Gałęziowe propozycje zaopatrzenia produkcyjnego rolnictwa w makroregionach - Śniegowska, Danuta (Wydział Prawa i Administracji UAM, 1979)
In studies on branch proportions of production supply to agriculture in regions a two-dimensional balance model has been used, in which branch and spatial systems have been taken into considerations. Acceptance of functional dependence of expenditures- on materials and production services to agriculture upon agricultural incomes was based on statistical analysis results. Analytical examination of proportions of production supply to agriculture was carried out in 1976, i.e. in the best representative year of agricultural output in Poland in the seventies. The fixed proportions of branch production supply to agriculture in macro regions in 1976 were used for determination for the next year of spatially differentiated agricultural output as well as indispensable size of production supply in macro-regions adequate to different agricultural output. The article is above an empirical presentation of a theoretical model of balancing production supply in a branch-spatial approach. The model was published in the Poznań Economic Annals, Vol. 29.
Branch Proportions of Production Supply to Agriculture in Regions